PROVERBIOS Y SENTENCIAS EN HISTORIA APOLLONII REGIS TYRI - Bérchez Castaño, Esteban (Proverbium - Yearbook, 2017)
The Story of Apollonius King of Tyre is an anonymous account from the 5th or 6th century A.D., often considered as pertaining to the adventure genre. It is not a work of high literary quality: on the contrary, the Latin used is rather poor and full of repetitions and inconsistencies. However, this novella greatly influenced subsequent literature, perhaps owing to its popular nature which gives it a certain degree of timelessness. The proverbs included in the book are further evidence of such popularity. We believe their study provides interesting information and sheds some light on some of the questions surrounding this literary work.